2007
DOI: 10.1007/s00464-007-9548-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural-orifice transgastric endoscopic peritoneoscopy in humans: Initial clinical trial

Abstract: Transgastric diagnostic peritoneoscopy is safe and feasible. This study demonstrates the initial steps of NOTES in humans, providing a potential platform for incisionless surgery. Technical issues, including instrumentation, visualization, intra-abdominal manipulation, and gastric closure need further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
128
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(135 citation statements)
references
References 8 publications
4
128
0
3
Order By: Relevance
“…Patients seem to be early adopters of the technology, perhaps owing to a perception that surgical risk is related to incision size, whereas surgeons prefer to wait for more safety and efficacy outcome data. 32 Years after NOSCAR published the white paper on NOTES in 2005, and although various NOTES procedures have now been tested in humans, 25,26,[33][34][35][36] investigators continue to rely on animal models to better understand and overcome several of the barriers precluding NOTES from wide clinical adoption. In brief, we have shown the feasibility of transcolonic NOTES peritonoscopy and abscess drainage in a canine survival study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients seem to be early adopters of the technology, perhaps owing to a perception that surgical risk is related to incision size, whereas surgeons prefer to wait for more safety and efficacy outcome data. 32 Years after NOSCAR published the white paper on NOTES in 2005, and although various NOTES procedures have now been tested in humans, 25,26,[33][34][35][36] investigators continue to rely on animal models to better understand and overcome several of the barriers precluding NOTES from wide clinical adoption. In brief, we have shown the feasibility of transcolonic NOTES peritonoscopy and abscess drainage in a canine survival study.…”
Section: Resultsmentioning
confidence: 99%
“…2,11,[23][24][25][26] Our study introduces an "abscess" into the abdominal cavity to assess transcolonic peritonoscopy in this setting. Specifically, we wanted to examine our ability to adequately visualize important predetermined areas: the peritoneal reflection in the pelvis, sigmoid colon, appendix, midjejunum, right lobe of the liver, right subphrenic space, lesser curvature of the stomach and left hepatic space.…”
Section: Discussionmentioning
confidence: 99%
“…Se identificaron un total de 184 estudios que reportaban los resultados de los procedimientos quirúrgicos (intrabdominales) mediante NOTES incluyendo cuatro realizados en humanos en el 2007 [18][19][20][21][22][23][24][25][26][27] . Sólo uno fue comparativo, este estudio con un nivel de evidencia III-2, coteja la peritoneoscopia mediante NOTES con la laparoscopia diagnóstica en 10 pacientes con masas pancreáticas para estadificación mediante laparoscopia.…”
Section: Resultsunclassified
“…However, transgastric peritoneoscopy being developed by Kalloo et al [7,19] showed no association with serious infection or other complications in the peritoneal cavity during their longterm survival experiments. Furthermore, Hazey et al [20] reported that although contamination in the abdomen was documented, no clinically significant episode of the peritoneal cavity was observed without abscess formation or infectious complications during laparoscopic Roux-en-Y gastric bypass. From those findings, although the peroral TGLB required to add the artificial injury for normal organs, it will become one of alternatives to another LB methods.…”
Section: Discussionmentioning
confidence: 99%
“…This report was similar to our procedure and results. In clinical, Hazey et al [20] reported that LB was uneventfully performed from the transgastric access route in a patient who underwent a diagnostic laparoscopic evaluation of pancreatic mass. Steele et al [24] also reported that LB from segments II, III, or IVb under flexible transgastric peritoneoscopy during Roux-en-Y gastric bypass for morbid obesity was www.intechopen.com performed in 3 patients with only minor bleeding from the liver biopsy sites.…”
Section: Discussionmentioning
confidence: 99%